(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Iron is one of the most essential elements for life, playing a crucial role in both biological systems and industrial development. From a biological perspective, iron is vital for the formation of haemoglobin, which is responsible for transporting oxygen in our body. Without adequate iron, the body cannot produce enough healthy red blood cells, leading to conditions such as Iron Deficiency Anaemia. From an industrial point of view iron is the backbone of modern civilization. It is the primary component of steel, which is used extensively in construction, transportation, machinery, and infrastructure. From buildings and bridges to automobiles etc. The Solvent extraction of Fe (III) from hydrochloric acid can be accomplished with various neutral organophosphorus compounds such as TBP, TOPO and other oxygen containing solvents such as alcohols, esters, ketones, dichloroether. The paper describes the extractive determination of iron using sodium salicylate with TEHP as the extractant. Iron Fe³⁺ is a hard Lewis acid (high charge density) and TEHP has a phosphoryl oxygen (P=O) that acts as a strong donor ligand. The bulky 2-ethylhexyl groups in TEHP increase electron donation to the P=O group, enhancing its complexation ability with Fe³⁺. Compared to other organophosphorus extractants such as tributyl phosphate (TBP) and acidic extractants (e.g., D2EHPA), TEHP exhibits higher extraction efficiency and selectivity toward Fe³⁺, particularly under moderate acid conditions. Its enhanced hydrophobicity and branched structure contribute to improved phase separation, reduced third-phase formation, and higher metal loading capacity. These properties make TEHP more suitable for the present extraction system.